Peranan Guru PAK dalam Penanaman Nilai-nilai Peranan Guru PAK dalam Penanaman Nilai-nilai - Nurlela Syafrian Oematan (Sekolah Tinggi Teologia Kerusso Indonesia, 2020)
The development of information and communication technology in the current digital era is growing very rapidly and affects many aspects of human life, including aspects of children's education. The influence of these technological developments also brings changes to modern lifestyles that have both positive and negative impacts on all levels of society, including the lives of children. The COVID-19 pandemic that has occurred since 2020 also affected the life of the education world, namely changing learning methods of the teaching and learning process in schools. The online learning method is starting to be applied for schools that are ready with this online learning system, which requires a lot of media, such as cellphones, laptops, computers and of course the availability of a good internet network. This government policy came into effect in several provinces in Indonesia on Monday, March 16, 2020, which was also followed by other provincial areas. The changing era and the influence of the development of technology and information can affect children's lives. These are a challenge for a teacher because the teacher's role is very important in the child's education process. This role can be interpreted as individual behavior that is important for the social structure of society. While facing all challenges, the teacher has important role to instill the right character values for students to anticipate all negative influences that can be caused and affect their lives, especially for PAK teachers in carrying out their main duties.